Diseases and Parasites of the Bobwhite - Forest E. Kellog; Gary L. Doster (National Quail Symposium Proceedings, 2017)
The authors' experiences with disease and parasite problems of wild and pen-raised bobwhites are given. Information extrapolated from an extensive literature review is presented in tabular form. Diseases and parasites of bobwhites, location in the bird of the lesion or parasite, and geographic areas of occurrence are note.